2018
DOI: 10.7759/cureus.3799
|View full text |Cite
|
Sign up to set email alerts
|

Utilizing Audience Response to Foster Evidence-based Learning in a Pilot Study: Does It Really Work?

Abstract: Introduction Radiology residency programs are increasingly using audience response systems (ARS) in educational lectures. It is imperative that this is investigated to assess if learning outcomes in trainees are actually improved. Methods The primary objective of this randomized prospective unblinded pilot study was to assess the effect of ARS on long-term learning outcomes, with a secondary objective of understanding perceptions of ARS amongst radiology residents. Twenty-two r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 9 publications
0
5
0
Order By: Relevance
“…Fourteen studies dealt with undergraduate students of medical, dental, and allied health sciences, whereas 8 studies dealt with residents and interns [Tables 1 and 2 ]. [ 12 13 14 15 16 17 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 ]…”
Section: Resultsmentioning
confidence: 99%
“…Fourteen studies dealt with undergraduate students of medical, dental, and allied health sciences, whereas 8 studies dealt with residents and interns [Tables 1 and 2 ]. [ 12 13 14 15 16 17 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 ]…”
Section: Resultsmentioning
confidence: 99%
“…[31][32][33][34][35] Gamified learning strategies have made inroads in radiology education, including such tools as in-lecture audience response systems, resident or fellow leaderboards, game fiction scenarios and roleplaying, and positive reinforcement with performance rewards for trainees. [36][37][38][39] We intentionally gamified the #ASHNRCOTW initiative to rely on audience submission of GIF images as the primary means of participation. The benefits of using GIF images are 3-fold: 1) Participants can drop hints at the correct answer without spoiling it for other participants, 2) participants weave a storylike tapestry of memorable GIF images that combine narrative and flashbulb episodic memory with factual medical information (semantic memory) to augment learning, and 3) GIF images offer a lighthearted and often comical vehicle for approaching learning, which adds to the enjoyment of participation.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have shown that an audience response system is an effective and engaging tool in medical education [5][6][7][8][9]. Kung et al [7] found that surveyed radiology residents believed they learned better from lectures that incorporated an audience response system, felt more comfortable answering questions via an audience response system, and were more likely to attend a lecture that incorporated an audience response system.…”
Section: Audience Response Systemmentioning
confidence: 99%
“…Lecturers have claimed that inserting questions can disrupt the flow of a lecture, that an audience response system requires more time investment and expertise, and that many systems only allow for multiple-choice or true/false questions [8,10]. In addition, the long-term effect on learning is controversial [5,6,11]. Awan et al [5] found that when residents were examined at baseline and 8 months following on a series of musculoskeletal radiology lectures, there was no statistical difference in the test scores between the group that received instruction using an audience response system and the group that did not.…”
Section: Audience Response Systemmentioning
confidence: 99%
See 1 more Smart Citation